MORPHOLOGICAL ASSESSMENT OF VARIOUS MATERIALS ROOT CANAL ON THE FABRIC OF THE NEUROVASCULAR BUNDLE MANDIBLE - A. V. Arutyunov; A. V. Elizarov (Кубанский научный медицинский вестник, 2014)
The study evaluated the morphological changes that occur in the neurovascular bundle rabbits under the influence of various materials used in root canal at 1, 6 and 12 months from the start of the experiment. In the experiment were prepared and studied rabbits jaws blocks 84 and 600 histological sections.